Five-year outcomes following PCI with DES versus CABG for unprotected LM coronary lesions: meta-analysis and meta-regression of 2914 patients Desfechos de 5 anos do tratamento de lesões de TCE por stents farmacológicos versus CRM: metaanálise e meta-regressão de 2914 pacientes - Michel Pompeu Barros de Oliveira Sá (Brazilian Journal of Cardiovascular Surgery, 2013)
OBJECTIVE: To compare the safety and efficacy at long-term follow-up of coronary artery bypass grafting (CABG) with percutaneous coronary intervention (PCI) using drug-eluting stents (DES) in patients with unprotected left main coronary artery (ULMCA) disease. METHODS: MEDLINE, EMBASE, CENTRAL/CCTR, SciELO, LILACS, Google Scholar and reference lists of relevant articles were searched for clinical studies that reported outcomes at 5-year follow-up after PCI with DES and CABG for the treatment of ULMCA stenosis. Five studies (1 randomized controlled trial and 4 observational studies) were identified and included a total of 2914 patients (1300 for CABG and 1614 for PCI with DES). RESULTS: At 5-year follow-up, there was no significant difference between the CABG and PCI-DES groups in the risk for death (odds ratio [OR] 1.159, P=0.168 for random effect) or the composite endpoint of death, myocardial infarction, or stroke (OR 1.214, P=0.083). The risk for target vessel revascularization (TVR) was significantly lower in the CABG group compared to the PCI-DES group (OR 0.212, P<0.001). The risk of major adverse cardiac and cerebrovascular events (MACCE) was significantly lower in the CABG group compared to the PCI-DES group (OR 0.526, P<0.001). It was observed no publication bias about outcomes and considerably heterogeneity effect about MACCE. CONCLUSION: CABG surgery remains the best option of treatment for patients with ULMCA disease, with less need of TVR and MACCE rates at long-term follow-up. OBJETIVO: Comparar segurança e eficácia do seguimento a longo prazo da cirurgia de revascularização miocárdica (CRM) com intervenção coronária percutânea (ICP), utilizando stents farmacológicos (SF) em pacientes com lesão de tronco de coronária esquerda não-protegida (TCE). MÉTODOS: MEDLINE, EMBASE, CENTRAL/CCTR, SciELO, LILACS, Google Scholar e listas de referências artigos relevantes foram escaneados para estudos clínicos que relataram resultados em 5 anos de seguimento após ICP-SF eCRM para o tratamento de lesão de TCE. Cinco estudos (um de ensaio clínico randomizado e quatro estudos observacionais) foram identificados e incluíram um total de 2914 pacientes (1300 para CRM e 1614 para ICP-SF). RESULTADOS: Aos 5 anos de seguimento, não houve diferença significativa entre os grupos CRM e ICP-SF no risco de morte (odds ratio [OR] 1,159, P=0,168) ou desfecho composto de morte, infarto do miocárdio , ou AVC (OR 1,214, P=0,083). O risco de necessidade de nova revascularização foi significativamente menor no grupo CRM em comparação com o grupo de ICP-SF (OR 0,212, P<0,001). O risco de eventos adversos cardíacos maiores e cerebrovasculares (EACMC) foi significativamente menor no grupo CRM em comparação com o grupo de ICP-SF (OR 0,526, P<0,001). Não foi observado viés de publicação sobre os resultados e considerável heterogeneidade dos efeitos sobre EACMC. CONCLUSÃO: CRM continua sendo a melhor opção de tratamento para pacientes com lesão de TCE, com menos necessidade de novas revascularizações e EACMC no seguimento a longo prazo.